GAMBARAN TATA KELOLA RUMAH SAKIT MENUJU SMART HOSPITAL DI RUMAH SAKIT TK.II 14.05.01 PELAMONIA KOTA MAKASSAR TAHUN 2023 - Trigriselda Datuan; Darmawati Junus; Dian Ekawaty; Ryryn Suryaman Prana Putra (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Hospital governance which focuses on hospital management using the hospital information system (SIMRS). With this information system, hospital governance plays an important role so that it becomes a smart hospital which previously still used a manual system so that it becomes electronic at Tk.II Hospital 14.05.01 Pelamonia so that the realization of a hospital that carries out smart hospital functions in the hospital governance system which optimizes the hospital information system (SIMRS). The aim of this research is to find out how hospital governance is towards a smart hospital in terms of Transparency (openness), Accountability (accountability), Responsibility (responsibility), Independence (independence), Fairness (justice).The research method used in this research is qualitative research with a descriptive approach in the form of written or spoken words, with the number of informants in this research being 8 people with this research data obtained through in-depth interview observations carried out directly and documentation studies during the research taking place.The results of the research show that Tk.II Hospital 14.05.01 Pelamonia has implemented the principles of Hospital Governance in realizing a smart hospital seen from transparency with the delivery of information, clear and timely, accountability with responsibility achieved and managing the hospital so that it is carried out effectively, independence in managing the hospital is professional with no pressure from other parties, and also the principle of hospital fairness is also in equalizing each employee fairly and evenly.